2022
DOI: 10.1021/acsbiomaterials.1c01265
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Hybrid Nanoink for 3D Bioprinting of Heterogeneous Tumor Models

Abstract: Despite the rapid progress in applying three-dimensional (3D) printing in the field of tissue engineering, fabrication of heterogeneous and complex 3D tumor models remains a challenge. In this study, we report a hybrid nanoink (AGC) composed of alginate, gelatin methacryloyl (GelMA), and cellulose nanocrystal (CNC), designed for multinozzle microextrusion 3D printing of tumor models. Our results show that the ink consisting of 2 wt % alginate, 4 wt % GelMA, and 6 wt % cellulose nanocrystals (AGC246) possesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…As this natural polymer provides a suitable environment for cell growth, inks composed of such material have been employed to design several tissue-like systems or models (tumor, skin, muscle) [112][113][114]. A noteworthy example developed a heterogeneous tumor system based on a composite ink consisting of gelatin, alginate and cellulose.…”
Section: Gelatin As Bioink For 3d Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…As this natural polymer provides a suitable environment for cell growth, inks composed of such material have been employed to design several tissue-like systems or models (tumor, skin, muscle) [112][113][114]. A noteworthy example developed a heterogeneous tumor system based on a composite ink consisting of gelatin, alginate and cellulose.…”
Section: Gelatin As Bioink For 3d Printingmentioning
confidence: 99%
“…The construction demonstrated that the gelatin-based ink was suitable for printing various cell types within different shapes of the 3D system in vitro. Specifically, alginate and gelatin were responsible for biocompatibility and adhesion, respectively, while cellulose provided mechanical strength [114].…”
Section: Gelatin As Bioink For 3d Printingmentioning
confidence: 99%
“…Gelatin has also been used to produce GelMA, which is a popular bioink that enhances the mechanical capabilities of gelatin through photo-crosslinking. 50 Tang et al 51 reported a multinozzle micro-extrusion 3D bioprinting process using alginate, GelMA, and cellulose nanocrystals (CNCs) for colorectal cancer treatment models. Moreover, glioblastoma models have frequently been produced using protein-based bioinks containing gelatin, fibrinogen, and thrombin.…”
Section: Composition Of Bioinksmentioning
confidence: 99%
“…Hydrogels with Different Stiffness. GelMA, as an acrylamide-modified gelatin (local hydrolysate of collagen) with excellent biological characteristics, has been widely used to resemble the microenvironment of multiple solid tumors, 32,34,35 and also acts as a mechanical interaction mimic platform as reported 36 although it may not be sufficient to accurately describe collagen biochemistry. From a processing perspective, GelMA hydrogels with tunable mechanical properties can be easily constructed by adjusting the UV exposure time and concentrations.…”
Section: Fabrication and Characterization Of Gelmamentioning
confidence: 99%